26. SOME FACTORS RELATED TO THE SEVERITY OF SEPSIS IN TERM NEONATES AT THE NATIONAL CHILDREN’S HOSPITAL, 2020 (Vietnam Journal of Community Medicine, 2023)
Objectives: Analyze and identify some factors related to the severity of neonatal sepsis at the National Children’s Hospital 2020. Methods: The study was designed using descriptive method with case series analysis. Results: The term neonates with mechanical ventilation at the front-line were at 3.2 times higher risk of death than those without mechanical ventilation at the front-line, with OR, 95%CI: 3.2 (1.6 -12.9). The neonates with mechanical ventilation at the National Children’s Hospital had a 27.7 times higher risk of death than the non-ventilated group, with OR, 95%CI: 27.7 (3.5-217.8). The neonates requiring catheterization were 21.1 times more likely to die than those without catheters, with OR, 95%CI: 21.1 (2.7-166.1). The group of neonatal sepsis with shock had a 5.1 times higher risk of death than those without shock, with an OR, 95%CI:5.1(1.9-14). Low white blood cell count was associated with mortality, with OR, 95%CI: 4.8 (4.8 - 16.5). The neonates with a platelet count < 100x109/L (thrombocytopenia) had a 4.2 times higher risk of death than those without thrombocytopenia, with OR, 95%CI: 4.2 (1.5-11.7). Conclusions: Factors associated with the severity of sepsis in term neonates included mechanical ventilation, catheterization, septic shock, leukocytosis, and thrombocytopenia.
Keywords: Sepsis, neonates, full term.